2017
DOI: 10.17925/eoh.2017.13.02.114
|View full text |Cite
|
Sign up to set email alerts
|

Can we Continue to Afford Access to Cancer Treatment?

Abstract: O ncology is facing a crisis of affordability that is not sustainable. The economic burden of cancer is growing, as a result of the rising cancer incidence and increased survival, alongside growing investment in disease prevention, diagnosis and treatment. The prices of new cancer drugs continue to increase, placing growing pressure on many healthcare systems. The aim of this article is to explore the reasons why the cost of cancer care is increasing, and why this increase may become unsustainable unless chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…The current situation and consequences of reaching the sustainability ceiling (where costs of treatment outweigh the benefits), including definitions of sustainability and value, are discussed further in the first and second articles in this series of three perspectives. 4,5 To regulate spending and allow continued -or even improved -access to cancer treatments, changes must be made before the sustainability ceiling is reached. 4,5 As detailed in the first two articles of this series, the continuing exponential rise in costs is driven, in part, by the introduction of a large number of new, high-cost treatments.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The current situation and consequences of reaching the sustainability ceiling (where costs of treatment outweigh the benefits), including definitions of sustainability and value, are discussed further in the first and second articles in this series of three perspectives. 4,5 To regulate spending and allow continued -or even improved -access to cancer treatments, changes must be made before the sustainability ceiling is reached. 4,5 As detailed in the first two articles of this series, the continuing exponential rise in costs is driven, in part, by the introduction of a large number of new, high-cost treatments.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 To regulate spending and allow continued -or even improved -access to cancer treatments, changes must be made before the sustainability ceiling is reached. 4,5 As detailed in the first two articles of this series, the continuing exponential rise in costs is driven, in part, by the introduction of a large number of new, high-cost treatments. Although innovation and research into new treatments should be encouraged, additional focus is needed on value-based medicine, characterised by evidence-based medicine, patient-centred care and cost-effectiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 For instance, a study of over 19,000 patients with melanoma found that while first-line, molecularlytargeted combination therapy for B-Raf proto-oncogene serine/threonine kinase (BRAF)-mutated metastatic melanoma was registered in 75% of Western European countries and fully reimbursed in 58%, the same treatment was registered in 42% of Eastern European countries and only reimbursed in 18%. In Eastern Europe, most patients are still treated with palliative chemotherapy that does not prolong overall survival.…”
mentioning
confidence: 99%
“…The first paper addresses the reasons why the cost of cancer care is increasing and why this may be unsustainable unless changes are made. 15 …”
mentioning
confidence: 99%